Strategic Successive Harvesting of Rocket and Spinach Baby Leaves Enhanced Their Quality and Production Efficiency - Filippos Bantis; Chrysos Kaponas; Charalambos Charalambous; Athanasios Koukounaras (Agriculture, 2021)
Rocket and spinach baby leaves are valuable commodities since they are basic components of popular ready-made salads. Two methods may follow after harvesting: establishment of new cultivations or successive revegetations and harvests. This study aimed to investigate the yield and nutritional value of rocket and spinach baby leaves after individual cultivations or successive revegetations in a floating system to improve their production strategy. The crops were cultivated in a greenhouse for seven weeks using a floating system with an adjusted nutrient solution. The leaves were either harvested and immediately replaced with a new set of plants (control) or harvested and placed again in the same tank in order to revegetate (revegetation). Revegetated rocket baby leaves in five cuts produced similar yield, with greater antioxidant capacity (DPPH scavenging activity) and total phenolic content, and greater nitrate content (eight times below the maximum allowed by EU) compared to control. Revegetated spinach produced more yield with enhanced antioxidant activity and total phenolic content and the same nitrate content compared to the control. Colour was not affected in either crop, thus eliminating the possibility for market rejection. Production efficiency was increased, as shown by the yields and the reduced resources provided in the revegetation tank. Thus, successive harvesting and revegetation are suggested for increased production efficiency and quality of rocket and spinach baby leaves.